Learn Ansible automate your cloud infrastructure, security configuration, and application deployment with Ansible - McKendrick, Russ (Packt Publishing Ltd., 2024)
Are you tired of manually deploying and managing your infrastructure and looking for ways to streamline your deployments, introduce consistency and collaboration, and save time? If so, then Learn Ansible is for you. Written by a DevOps practitioner and system administrator with 30+ years of experience, this book will teach you how to automate repetitive tasks and effortlessly manage several resources from a single code base. From installing Ansible and writing your first playbook to deploying multi-tier applications across different cloud platforms, this book will take you on an exciting learning journey. By learning the art of defining highly available cloud infrastructure using code, you'll find it easy to distribute configurations alongside your application. You'll explore Ansible Galaxy, learn about community-contributed Ansible roles, and discover how to create and share your own roles. Later, the book delves into the capabilities of Ansible AWX and integrating Ansible with your CI/CD pipelines, using Azure DevOps and GitHub Actions. With real-world examples and hands-on tutorials, you'll build a solid foundation to tackle any automation project. By the end of this book, you'll be able to confidently implement Ansible in your environment and day-to-day workflows, taking your deployments to the next level.
Includes bibliographical references and index
Keywords: Information technology -- Automation; Information technology -- Management; Computer networks -- Security measures -- Management; Cloud computing; Technologie de l'information; Automatisation; Technologie de l'information; Gestion; Réseaux d'ordinateurs; Sécurité; Mesures; Gestion